RNA Catabolites Contribute to the Nitrogen Pool and Support Growth Recovery of Wheat - Melino, Vanessa Jane; Casartelli, Alberto; George, Jessey; Rupasinghe, Thusitha; Roessner, Ute; Okamoto, Mamoru; Heuer, Sigrid (Frontiers in Plant Science, 2018)
Turn-over of RNA and catabolism of nucleotides releases one to four ammonia molecules; the released nutrients being reassimilated into primary metabolism. Preliminary evidence indicates that monocots store high levels of free nucleotides and nucleosides but their potential as a source of internal organic nitrogen for use and remobilisation is uncharted. Early tillering wheat plants were therefore starved of N over a five-day time-course with examination of nucleic acid yields in whole shoots, young and old leaves and roots. Nucleic acids constituted ~4% of the total N pool of N starved wheat plants, which was comparable with the N available from nitrate (NO3-) and greater than that available from the sum of 20 proteinogenic amino acids. Methods were optimised to detect nucleotide (purine and pyrimidine) metabolites, and wheat orthologs of RNA degradation (TaRNS), nucleoside transport (TaENT1, TaENT3) and salvage (TaADK) were identified. It was found that N starved wheat roots actively catabolised RNA and specific purines but accumulated pyrimidines. Reduced levels of RNA corresponded with induction of TaRNS2, TaENT1, TaENT3, and TaADK in the roots. Reduced levels of GMP, guanine, xanthine, allantoin, allantoate and glyoxylate in N starved roots correlated with accumulation of allantoate and glyoxylate in the oldest leaf, suggesting translocation of allantoin. Furthermore, N starved wheat plant exogenously supplied with N in the form of purine catabolites grew and photosynthesised as well as those plants re-supplied with NO3-. These results support the hypothesis that the nitrogen and carbon recovered from purine metabolism can support wheat growth.